Cutaneous polyarteritis nodosa: Diagnosis lies skin deep - Raghavendraswami Amoghimath; Rajwanti K Vaswani; Chandrahas T Deshmukh; Chhaya Divecha (Wolters Kluwer Medknow Publications, 2018)
Cutaneous polyarteritis nodosa (CPAN) is an uncommon form of cutaneous vasculitis. Definitive diagnosis is based on skin biopsy. We present a rare case of CPAN in a 2-year-old male child who presented with a history of fever, cutaneous ulcers, and digital gangrene. He was treated with steroids and skin lesions had resolved completely. CPAN needs to be differentiated from systemic polyarteritis nodosa for specific prognosis and management. We report this case to highlight the need of early diagnosis for faster recovery with favorable outcome.